Proposing a Socioculturally-informed Syllabus to Teach Paragraph Writing for Iranian Undergraduate EFL learners: Materials, Methods and Assessment - Omid Mallahi; Mahboobeh Saadat (Journal of Modern Research in English Language Studies)
Due to the importance of humanistic and learner-centered views of language teaching, many instructors and curriculum planners are sensitive of the learners’ needs in creating tailor-made instructional programs and designing effective syllabus for their courses. Accordingly, the present study used a needs analysis procedure to inspect a group of Iranian undergraduate EFL learners’ problems and needs in writing. In fact, the primary stakeholders’ (i.e., 58 learners and 3 writing instructors) views regarding the students’ difficulties in writing and their expectations and suggestions regarding the roles and effects of the writing course, instructors and the materials on resolving their problems and, thus, improving their writing ability were explored by using two sets of open-ended surveys. Subsequently, in light of the findings of the study a socioculturally-informed syllabus, which can guide the selection of materials, teaching methods and assessment techniques in a writing course, was proposed and elaborated upon. Insights provided by the present study can be useful for writing teachers, researchers, and possibly syllabus designers and curriculum planners, to design an appropriate and accountable writing course for their learners to identify and resolve their problems and, thus, enhance their writing quality.